The Re-creation of Vancouver’s Japanese Community, 1945–2008 - Roy, Patricia (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2008)
AbstractIn 1942, the approximately 8,500 Japanese Canadian residents of Vancouver, like all other Japanese Canadians, were required to leave the coast. With limited exceptions, they could not return until 1 April 1949. Early returnees began to recreate a community; later, Japanese Canadians too young to remember the war and a handful of new immigrants reclaimed pride in the Japanese Canadian heritage. The re-created community is no longer an identifiable physical place; Japanese Canadians are scattered throughout Vancouver and its suburbs. The history of the Japanese Canadian Citizens Association (JCCA) shows how, with difficulty and with some conflict over the advisability of retaining a Japanese identity, Japanese Canadians re-created a society whose members simultaneously take pride in their Japanese Canadian heritage and fully participate in the larger community of greater Vancouver.